The Relationship Between Phosphodiesterase-5 Inhibitors and Nonarteritic Anterior Ischemic Optic Neuropathy - Pomeranz, Howard D. (Journal of neuro-ophthalmology, 2016)
A cause and effect relationship between phosphodiesterase-5 inhibitor (PDE5I) use and nonarteritic anterior ischemic optic neuropathy (NAION) has been hypothesized based on case reports. Review of literature. Thirty-nine case reports in the peer-reviewed medical literature have documented a possible relationship between PDE5I consumption and NAION. However, pertinent details, such as the dose and frequency of PDE5I use, and elapsed time between ingestion and onset of vision loss, are lacking from many of these reports. Investigations regarding alterations in ocular perfusion in research subjects who ingested sildenafil have been inconclusive because they have not been performed on subjects with "disc at risk" or risk factors for NAION. One case-crossover study demonstrated a 2-fold increase in risk of NAION after ingestion of PDE5I. When a diagnosis of NAION is made, an inquiry should be made as to whether any PDE5I was ingested before the onset of vision loss. If so, the patient should be counseled regarding the possibility that continued PDE5I use may increase the risk of NAION in the fellow eye. Patients with a known history of previous NAION should be cautioned regarding the use of PDE5I for erectile dysfunction or pulmonary hypertension because of the potential increased risk of fellow eye involvement.